Dispositivo para controle populacional de insetos: com ênfase no aedes aegypti - Lima, Fabio Pereira de (2019)
Due to the frequent epidemics caused by the Aedes aegypti mosquito, many control and monitoring procedures are used. The former are characterized by the possibility of possible intoxication and the latter by inaccuracy. Therefore, the objective of this work was a brief research on the use of odorants (artificial kairomones) to attract insects and the development of an electronic trap capable of not only exterminating the insect but also able to count/estimate these events. The trap controls the dispersion of the odorant solution by ultrasound and exterminates them by means of electrical discharge promoted by a high voltage electrified barrier from a flyback converter. The consolidation of this device consisted of the development of a flyback DC-DC converter operating in 25 kHz MDC and for the nebulizer, a Colpitts oscillator for a 1, 7 MHz piezoelectric transducer. However, due to unavailability of these resources, the research followed bench tests to evaluate physical responses visually and through measuring instruments. The devices proved to be effective as expected and especially capable of allowing their control and monitoring via remote digital signals, thus enabling in the future the integration of this circuit developed in dengue vector monitoring and control networks or even crop insects.